Topological metamaterial plates: Numerical investigation, experimental validation and applications. (15th January 2023) - Ni, Anchen; Shi, Zhifei
Highlights: The concept of topological insulator is introduced into plates in civil engineering. Topological and conventional interface states of flexural waves are obtained. The influence of key parameters on interface states is comprehensively discussed. Interface states show robustness against defects and material damping. 3D-printed topological metamaterial plates are fabricated and tested. The feasibility of topological metamaterial plates to vibration mitigation is verified. Abstract: The concept of topological insulator is introduced into plates in civil engineering, and topologically protected interface states of flexural waves are obtained successfully. Thanks to the topological wave transport between two domains with distinct topological phases, this novel topological metamaterial plate will realize wave guiding and wave attenuation simultaneously. Interestingly, not only the topological interface state but also the conventional interface state appears at the specific topological interface. In addition, the influence of geometric and material parameters on the interface states and band gap is discussed in detail. The dynamic characteristics of this novel type of plate are studied by full-field simulation in the frequency domain, which exhibits high transmission efficiency and strong robustness against defects. To further verify the feasibility, two 3D-printed experimental plates are fabricated and tested, experimentally demonstrating these intriguing dynamic properties. Finally, by inputting the measured acceleration record of train-induced vibration, the performance of topological metamaterial plate to ambient vibration control is assessed in time domain. This study could facilitate the application of topological insulators, opening up a new window for vibration mitigation, energy harvesting and signal detection.